2014
DOI: 10.1177/1010539514529810
|View full text |Cite
|
Sign up to set email alerts
|

A Logistic Regression Model for Estimating Transport Accident Deaths Using Verbal Autopsy Data

Abstract: This study aimed to create an appropriate model using verbal autopsy (VA) data to estimate transport accident deaths from vital registration data in Thailand. A sample of 9644 VA deaths was obtained from the Thai Ministry of Public Health. VA assessed transport accidents accounted for 546 deaths (5.7% of sample). Logistic regression was used to model transport accident deaths classified by 9 provinces, 16 gender-age groups, 14 combinations of vital reported cause groups, and place of death (in or outside hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Applications of the method can be found in several other studies (18)(19)(20)(21). The proportion of the weighted sum contrasts does not involve selecting a reference group and it will give full information about confidence interval for comparing each proportion with the overall proportion.…”
Section: Methodsmentioning
confidence: 99%
“…Applications of the method can be found in several other studies (18)(19)(20)(21). The proportion of the weighted sum contrasts does not involve selecting a reference group and it will give full information about confidence interval for comparing each proportion with the overall proportion.…”
Section: Methodsmentioning
confidence: 99%
“…In this statistical model we assume w ∈ {0, 1}, where 0 represents a bad class and 1 a good class. Therefore, the logistic regression model defines X as the data set and θ as a vector of coefficients derived from maximum likelihood estimation [40].…”
Section: )mentioning
confidence: 99%
“…After the results of our logistic regression model, applied to the reference population, the deaths from POC and CM were found to be 1.49 times and 2.18 times higher than those reported in VR respectively. Klinjun et al [14] also found 1.68 to 2.65 times higher estimation in different gender/age groups due to a transport accident in Thailand in 2005. Although the child death rate has decreased substantially in recent years in Thailand, the number of reported child deaths has increased over the 14 years period.…”
mentioning
confidence: 94%
“…After reviewing all these articles, we found more scope for analyzing the same data and to develop an appropriate method to estimate deaths in the few years before and after the VA study. Using new methods, in the data, some papers have already been published focusing on deaths due to HIV/AIDS, transport accident and cancer in Thailand [13][14][15] and some others are in the process of review for publication. This paper is a part of the same study focusing only on 2 causes of child deaths as stated above in the 1 st paragraph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation